2016
DOI: 10.1523/jneurosci.2473-16.2016
|View full text |Cite
|
Sign up to set email alerts
|

Actions of Steroids: New Neurotransmitters

Abstract: Over the past two decades, the classical understanding of steroid action has been updated to include rapid, membrane-initiated, neurotransmitter-like functions. While steroids were known to function on very short time spans to induce physiological and behavioral changes, the mechanisms by which these changes occur are now becoming more clear. In avian systems, rapid estradiol effects can be mediated via local alterations in aromatase activity, which precisely regulates the temporal and spatial availability of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
61
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 81 publications
(65 citation statements)
references
References 158 publications
1
61
0
3
Order By: Relevance
“…Estradiol signaling rapidly induces neurotransmitter release [45, 8688] and regulates neurotransmission [89]. Indeed, estradiol (and steroid hormones in general) signaling through membrane receptors resembles GPCR neurotransmitter signaling [90]. Such analyses revealed that the initial action of estradiol, in terms of lordosis, is to engage an inhibitory circuit that involved MPN-projecting β-end neurons [84, 86].…”
Section: Membrane Estrogen Receptors Regulating Sexual Receptivitymentioning
confidence: 99%
“…Estradiol signaling rapidly induces neurotransmitter release [45, 8688] and regulates neurotransmission [89]. Indeed, estradiol (and steroid hormones in general) signaling through membrane receptors resembles GPCR neurotransmitter signaling [90]. Such analyses revealed that the initial action of estradiol, in terms of lordosis, is to engage an inhibitory circuit that involved MPN-projecting β-end neurons [84, 86].…”
Section: Membrane Estrogen Receptors Regulating Sexual Receptivitymentioning
confidence: 99%
“…Recent research demonstrated that steroids can function in a "neurotransmitter-like" way, being synthesized at precise spatial locations within neural circuits in the brain and acting within minutes as local neuromodulators that rapidly regulate cognitive functions and behavior [24][25][26][27].…”
Section: Non-genomic Actionmentioning
confidence: 99%
“…The modern understanding of a cell response to a steroid action is that it occurs within the same time frame as that of the G protein-coupled receptors influencing a variety of cellular functions such as gating membrane channels, increasing the intracellular calcium release, activating tyrosine-protein kinase (Src), MAPK, and others [27]. Many studies support a model of integrated signaling that couples signal transduction cascades to transcription in the nucleus, providing an integrated view of hormone signaling in the brain [32].…”
Section: Non-genomic Actionmentioning
confidence: 99%
“…Большое количество современных работ посвящено изучению влияния прогестерона на нервную ткань и функцию центральной нервной системы (ЦНС) [25,27,33]. Доказана способность прогестерона связываться с рецепторами к нему в ЦНС и модулировать поведение и настроение млекопитающих через геномный и неге-номный пути влияния [50]. Также прогестерон может синтезироваться в самой нервной системе, поэтому он еще классифицируется как нейростероид.…”
Section: другие биологические эффекты прогестеронаunclassified